Focus on the Mental Health of Pediatric Medical Workers in China After the COVID-19 Epidemic - Liu, Hui; Wang, Li (Frontiers in Psychology, 2021)
As was previously known, paediatric medical staff in China faced several hurdles including high occupational risk, multiple contradictions, heavy workload and long working hours. After the outbreak of 2019 novel coronavirus, facing the overload of work and the potential risk of infection, paediatric medical workers may be under great psychological pressure. The purpose of this article was to call attention to the impact of the epidemic on the mental health of Chinese paediatric workers, and developing psychological intervention programme that are tailored to them. The experiences from this public health emergency should inform the efficiency and quality of future crisis intervention of the Chinese government and authorities around the world.